VIRTUAL ELECTRONIC COMPONENTS OF THE ELECTRONIC EQUIPMENT - E. Lazarevich; U. Semak; Sh. Amzeev (Системный анализ и прикладная информатика)
The article is present new idea of the creation, developments and improvements of the electronic equipment of complex systems by means of the virtual electronic components. The idea of the virtual electronic components is a presentation and perception of the creation and developments of the equipment on two forming: real – in the manner of standard marketed block of the intellectual property and image – in the manner of virtual component. The real component in most cases slows the development of the electronic equipment. The imaginary component is the «locomotive» of development of the electronic equipment. The Imaginary component contains the scientific has brushed against developer. The scientific has brushed against developer reveals of itself in the manner of virtual component on the modern level of the design rates of microelectronics.